SDSS-IV MaNGA: The link between bars and the early cessation of star formation in spiral galaxies. Issue 1 (21st September 2020) - Fraser-McKelvie, Amelia; Merrifield, Michael; Aragón-Salamanca, Alfonso; Peterken, Thomas; Kraljic, Katarina; Masters, Karen; Stark, David; Fragkoudi, Francesca; Smethurst, Rebecca; Fraser Boardman, Nicholas; Drory, Niv; Lane, Richard R
ABSTRACT: Bars are common in low-redshift disc galaxies, and hence quantifying their influence on their host is of importance to the field of galaxy evolution. We determine the stellar populations and star formation histories of 245 barred galaxies from the Mapping Nearby Galaxies at APO (MaNGA) galaxy survey, and compare them to a mass- and morphology-matched comparison sample of unbarred galaxies. At fixed stellar mass and morphology, barred galaxies are optically redder than their unbarred counterparts. From stellar population analysis using the full spectral fitting code starlight, we attribute this difference to both older and more metal-rich stellar populations. Dust attenuation however, is lower in the barred sample. The star formation histories of barred galaxies peak earlier than their non-barred counterparts, and the galaxies build up their mass at earlier times. We can detect no significant differences in the local environment of barred and unbarred galaxies in this sample, but find that the H i gas mass fraction is significantly lower in high-mass ($\rm {M}_{\star } \gt 10^{10}~\rm {M}_{\odot }$ ) barred galaxies than their non-barred counterparts. We speculate on the mechanisms that have allowed barred galaxies to be older, more metal-rich and more gas-poor today, including the efficient redistribution of galactic fountain byproducts, and a runaway bar formation scenario in gas-poor discs. While it is not possible to fully determine the effect of the bar on galaxy quenching, we conclude that the presence of a bar and the early cessation of star formation within a galaxy are intimately linked.